2016
DOI: 10.3748/wjg.v22.i40.8862
|View full text |Cite
|
Sign up to set email alerts
|

Liver-targeted hydrodynamic gene therapy: Recent advances in the technique

Abstract: One of the major research focuses in the field of gene therapy is the development of clinically applicable, safe, and effective gene-delivery methods. Since the first case of human gene therapy was performed in 1990, a number of gene-delivery methods have been developed, evaluated for efficacy and safety, and modified for human application. To date, viral-vector-mediated deliveries have shown effective therapeutic results. However, the risk of lethal immune response and carcinogenesis have been reported, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Furthermore, non-clinical studies for liver gene delivery have benefitted from the use of hydrodynamic (tail vein) injection to mice, a highly efficient delivery strategy, which requires the injection of a relatively high volume of liquid carrying the gene therapy vector. This high volume (up to 10% of body weight in rodents) causes a congestion in the right ventricle allowing retrograde flow of the gene therapy liquid back through the portal vein [52] at significant pressure. It is this transient increase in hepatic pressure that ensures efficient vector delivery throughout the organ.…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…Furthermore, non-clinical studies for liver gene delivery have benefitted from the use of hydrodynamic (tail vein) injection to mice, a highly efficient delivery strategy, which requires the injection of a relatively high volume of liquid carrying the gene therapy vector. This high volume (up to 10% of body weight in rodents) causes a congestion in the right ventricle allowing retrograde flow of the gene therapy liquid back through the portal vein [52] at significant pressure. It is this transient increase in hepatic pressure that ensures efficient vector delivery throughout the organ.…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…Metabolic and genetic diseases, which show lower level of normal functional protein, are so far good candidates for this type of procedure. Although there is evidence showing transgene expression and that the procedure was safely performed in pigs [54][55][56][57], dogs [58,59], and baboons [60,61], further preclinical studies are necessary prior to human therapy application.…”
Section: Resultsmentioning
confidence: 99%
“…For its application in human, safety and efficacy of this approach have been extensively studied and improved. To date, various types of nucleic acid have been delivered by this approach in rodents as well as pigs [54][55][56][57], dogs [58,59], and rhesus monkeys [60,61]. Functional analyses of therapeutic gene were reported in nonalcoholic steatohepatitis [62], hepatitis B and C [63], fulminant hepatitis [64,65], liver fibrosis [66,67], liver regeneration [68], Fabry's disease [64], and colon cancer [69].…”
Section: Hydrodynamic Gene Delivery (Hgd)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, our knowledge regarding in vivo gene delivery targeting the pancreas and islets is currently very limited [3][4][5][6] , although many studies regarding in vivo gene delivery targeting other tissues including liver have been reported [7][8][9][10] . Even though this is a serious situation, Rehman et al reported that the adeno associated virus (AAV) 8-mediated gene transfer of interleukin-4 to pancreatic β cells prevents the onset of diabetes in non-obese diabetic mice 5 .…”
Section: Introductionmentioning
confidence: 99%